Benzo[c][1, 2, 5]thiadiazole derivatives: A new class of potent Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2) inhibitors. Issue 23 (1st December 2017) - Wang, Wen-Long; Chen, Xiao-Yu; Gao, Ya; Gao, Li-Xin; Sheng, Li; Zhu, Jingyu; Xu, Lei; Ding, Zhen-Zhong; Zhang, Chao; Li, Jing-Ya; Li, Jia; Zhou, Yu-Bo
Graphical abstract: Abstract: The Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2) is an oncogenic phosphatase linked to various kinds of cancers. Consequently, SHP2 has emerged as a promising target for novel anti-cancer agents. Using scaffold-hopping strategy, a series of benzo[ c ][1, 2, 5]thiadiazole derivatives was designed from PTP1B inhibitors with 1H -2, 3-Dihydroperimidine motif, synthesized and evaluated their biological activities against PTP1B and SHP2. Among them, the representative compound11g displayed SHP2 inhibitory activity with IC50 of 2.11 ± 0.99 μM, exhibited 2.02-fold and 25-fold selectivity for SHP2 over SHP1 and PTP1B respectively and had no visible activity against TCPTP. These preliminary results could provide a possible opportunity for the development of novel SHP2 inhibitors with optimal potency and improved pharmacological properties.